THE USE OF ‘RUNNING DICTATION’ GAME TO IMPROVE THE TENTH GRADERS OF VOCATIONAL HIGH SCHOOL’S SPEAKING SKILL” (RETAIN, 2016)
THE USE OF ‘RUNNING DICTATION’ GAME TO IMPROVE THE TENTH GRADERS OF VOCATIONAL HIGH SCHOOL’S SPEAKING SKILL” Hilyah Mardhiyah English Department, Faculty of Languages and Arts, State University of Surabaya Email: hilyahmardhiyah@mhs.unesa.ac.id Abstract Spoken English, unlike the written one, is very complex. It involves lots of features such as intonation, facial expression, etc. Therefore, it makes those who learn to speak anxious. This is also faced by the students of a vocational high school. To reduce the anxiety, it is necessary that the teacher use an entertaining and fun activities, one of which is Running Dictation game. This study aims to find out whether the use of Running Dictation game can improve the students’ speaking skill. Pre-experimental research is used in this research using one group pre-test-posttest design. The sample taken are 39 students of X Pastry 1 of SMKN 6 Surabaya. After the treatment, the result of the pretest and posttest are compared. It shows that the average score of pre-test is 46.67 and the posttest is 52.83, and the value of Sig. (2-tailed) is .006. In conclusion, the use of Running Dictation significantly improves the tenth graders of SMKN 6 Surabaya’s speaking skill. Keywords: Speaking, Game, Running Dictation game. Abstrak Berbicara bahasa Inggris, tidak seperti menulis, sangat kompleks. Berbicara melibatkan banyak fitur seperti intonasi, ekspresi wajah, dll Oleh karena itu, hal tersebut membuat mereka yang sedang belajar berbicara merasa cemas. Hal ini juga dihadapi oleh siswa Sekolah Menengah Kejuruan. Untuk mengurangi kecemasan, guru perlu menggunakan kegiatan pembelajaran yang menghibur dan menyenangkan, salah satunya permainan Running Dictation. Penelitian ini bertujuan untuk mengetahui apakah penggunaan permainan Running Dictation dapat meningkatkan keterampilan berbicara siswa. Penelitian pra-eksperimental digunakan dalam penelitian ini dan menggunakan desain pre-test-posttest satu kelompok. Sampel yang diambil adalah 39 siswa kelas X Pastry 1 dari SMKN 6 Surabaya. Setelah permainan diberikan, hasil pretest dan posttest dibandingkan. Hal ini menunjukkan bahwa nilai rata-rata pre-test adalah 46,67 dan posttest adalah 52,83, dan nilai Sig. (2-tailed) adalah 0,006. Kesimpulannya, penggunaan Running Dictation secara signifikan meningkatkan siswa kelas X keterampilan berbicara SMKN 6 Surabaya. Kata Kunci: Keterampilan berbicara, Permainan, Permainan Running Dictation